Zainab's traffic: moving saints, selves, and others across borders - Yıldız, Emrah (Atelier, 2024)
"What is the value-religious, political, economic, or altogether social-of getting on a bus in Tehran for its travelers who embark on an eight-hundred-mile journey to reach the Sayyida Zainab Shrine outside Damascus across two international borders? Under what material conditions can such values be established, reassessed, or transgressed, and by whom? Zainab's Traffic provides answers to these questions alongside the socially embedded-and spatially generative-encounters of ritual, mobility, desire, genealogy, and patronage along the route. Whether it is through the study of the spatial politics of saint veneration in Islam, analysis of cross-border gold trade and sanctions, or examination of pilgrims' desire for Syrian lingerie accompanying their pleas with the saint in marital matters, the book develops the idea of visitation as a ritual of mobility across geography, history, and category. Iranian visitors' experiences on the road to Sayyida Zainab-emerging out of a self-described "poverty of mobility"-demonstrate the utility of a more capacious anthropological understanding of ritual. Rather than thinking of ritual as a scripturally canonized manual for pious self-cultivation, Zainab's Traffic approaches ziyarat as a traffic of pilgrims, goods, and ideas across Iran, Turkey, and Syria"--